The quantitative lung index and the prediction of survival in fetuses with congenital diaphragmatic hernia. (March 2016) - Illescas, Tamara; Rodó, Carlota; Arévalo, Silvia; Giné, Carles; Peiró, José L.; Carreras, Elena
Abstract: Introduction: The lung-to-head ratio (LHR) is routinely used to select the best candidates for prenatal surgery and to follow-up the fetuses with congenital diaphragmatic hernia (CDH). Since this index is gestation-dependent, the quantitative lung index (QLI) was proposed as an alternative parameter that stays constant throughout pregnancy. Our objective was to study the performance of QLI to predict survival in fetuses with CDH. Materials and methods: Observational retrospective study of fetuses with isolated CDH, referred to our center. LHR was originally used for the prenatal surgery evaluation. We calculated the QLI and compared the performance of both indexes (QLI and LHR) to predict survival. Results: From January-2009 to February-2015 we followed 31 fetuses with isolated CDH. The mean QLI was 0.66 (95% CI: 0.57–0.75) for survivors and 0.41 (95% CI: 0.25–0.58) for non-survivors ( p < 0.01) and the mean LHR was 1.38 (95% CI: 1.17–1.60) for survivors and 0.91 (95% CI: 0.57–1.25) for non-survivors ( p < 0.02). All operated fetuses ( n = 12) had a LHR <1 and a QLI <0.5 and none of them survived when the QLI was <0.32. When separately considering the prenatal surgery status, the mean values of the QLI (but not those of the LHR) were still significantly different between survivors and non-survivors. The comparative ROC curves showed a better performance of the QLI with respect to the LHR for the prediction of survival, especially in the group of operated fetuses, although differences were not statistically significant. Comment: The QLI seems to be a better predictor for survival than the LHR, especially for the group of fetuses undergoing prenatal surgery.